Effect of tree portion and distance from pith on the physical properties of batai (Paraserianthes falcataria) / Suria Mohamad Akhir and Jamaludin Kasim - Mohamad Akhir, Suria; Kasim, Jamaludin (2011)
This study was conducted on the Paraserianthes falcataria (batai), to determine its basic properties and effects of tree portion and distance from pith. Three 8-year-old batai were obtained from the Forest Plantation at Dong Hwa Fiberboard, Merbok Kedah. Discs of 20mm thick were cut from bottom (30 cm above ground), middle (50% of clear bole height) and top (80% of clear bole height). From each portion samples (20mm x 20mm x 20mm) were according to three sections namely near bark, middle and near pith. The basic properties determined carried out according to the Technical Association of the Pulp and paper Industry Standard (TAPPI). Result shows the specific gravity of batai ranges from 0.15 to 0.31. It decreases with tree portion and increases with distance from pith. While the green moisture content of batai ranges from 280% to 550%. It increases from bottom to top portion and decreases from near pith to near bark.